Common due-window assignment for single-machine scheduling with generalized earliness/tardiness penalties and a rate-modifying activity. Issue 3 (4th March 2021) - Wang, Ji-Bo; Hu, Yang; Zhang, Bo
ABSTRACT: This article investigates the single-machine common due-window assignment problem with generalized earliness/tardiness penalties and a rate-modifying activity. Job processing times include two cases: one with constant values and another with time-dependent processing times (deterioration effect). Considering the maintenance activity, the maintenance time is a fixed constant. The goal is to determine the position of the common due window and the optimal sequence such that the following objective function is minimized: the weighted penalties for the sum of earliness and tardiness, the weighted number of early and delayed, and the weighted due-window starting time and size. It is proved that the problem can be solved in O ( n 6 ) time, where n is the number of jobs.